The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/jat.1687
|View full text |Cite
|
Sign up to set email alerts
|

Commercial naphthenic acids and the organic fraction of oil sands process water induce different effects on pro‐inflammatory gene expression and macrophage phagocytosis in mice

Abstract: Naphthenic acids (NAs) are believed to be the major toxic component of oil sands process water (OSPW). Different OSPW preparations have distinct NA compositions, and additional organics, that differ from the commercial NAs (C-NAs) often used for toxicology studies. To evaluate whether C-NAs are an adequate model to study OSPW toxicity in complex organisms, we compared the effects of C-NAs and the extractable organic fraction of OSPW (OSPW-OF) on mice immune mechanisms. Mice were orally exposed to different C-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…4) help to explain their vastly different microbial aerobic biodegradation rates [48] as well as the different toxicological effects that these mixtures elicit in exposed organisms. [20,49,50] The different compositions also raise questions about the common practice (including in our own studies [8] ) of semiquantifying NA concentrations in OSPW and natural waters using commercial NA mixtures as standards.…”
Section: Optimizing Chromatographic Separation Of Nasmentioning
confidence: 91%
“…4) help to explain their vastly different microbial aerobic biodegradation rates [48] as well as the different toxicological effects that these mixtures elicit in exposed organisms. [20,49,50] The different compositions also raise questions about the common practice (including in our own studies [8] ) of semiquantifying NA concentrations in OSPW and natural waters using commercial NA mixtures as standards.…”
Section: Optimizing Chromatographic Separation Of Nasmentioning
confidence: 91%
“…The adsorption of ions on the bitumen appeared to be saturated at 10 wt% solvent addition, as no further reduction in ion concentration of process water was observed with the further dilution of bitumen. However, the viscosity of the bitumen was shown to continue to decrease with further increasing dilution solvent dosage , allowing more surface active materials (i.e., carboxylic acids) to accumulate at the bitumen-water interface (Allen, 2008;Garcia-Garcia et al, 2012;Liu et al, 2002). Consequently, the zeta potential of the diluted bitumen became more negative with further increasing solvent dilution of bitumen (see Fig.…”
Section: Surface Charge Of Diluted Bitumen Droplets In Process Watermentioning
confidence: 91%
“…However, West et al has declared that the unknown impurities in C-NAs mixtures may limit the usefulness of C-NAs for toxicity assays [55]. And also, Garcia-Garcia et al compared the effects of C-NAs and OSPW NAs in the pro-inflammatory genes expressions in mice, and found that C-NAs may not necessarily reflect the possible effects induced in organisms [56]. In the current study, we studied the endocrine disruption in vitro and in vivo assays with OS-NAs and C-NAs.…”
Section: Discussionmentioning
confidence: 95%